The Ethiopian clubs: the development of social institutions and identities amongst Ethiopians in Johannesburg - Yimer, Amel Belay (My University, 2012)
This research examines cultural institutions (i.e. savings groups and social associations) amongst Ethiopian women in Johannesburg. By examining these institutions, the research will focus on the transference and practice of cultural institutions in a foreign setting and the relation it bears to maintaining identity. The research then self reflexively discusses these findings in a short documentary entitled The Coffee Drinkers. Johannesburg has a burgeoning Ethiopian population where their professional and social lives are reinstated and reconstructed based on the new environment they find themselves in. Jeppe Street in the Central Business District of Johannesburg is mainly populated by Ethiopians and is a fertile ground where all dynamics involved in physical and social displacement, including those between loss of familiar support structures and changes reflected identity thereafter, come to surface. While the functions of these selected cultural institutions vary, they share a similarity in their objective to strive and collectively help its members within a community as well as strengthen bonds between them. This is done through a series of actions which include meeting regularly, living up to roles and responsibilities prescribed but the community and creating a space where members can communicate and share their experiences. The above mentioned groups are chosen as examples of such functions. This research reveals the new significance that cultural institutions such as hold for Ethiopian women in Johannesburg in line with their adopted routines, lifestyles and associated practicalities. The hegemonic reconstructions that exist within the Ethiopian Diaspora, along with its emergent and residual aspects are outlined. The Coffee Drinkers contributes to collective knowledge about Ethiopians in Johannesburg with emphasis on the psycho social and community-life based processes they practice.
M.A. University of the Witwatersrand, Faculty of Humanities, 2012